2017
DOI: 10.5487/tr.2017.33.2.097
|View full text |Cite
|
Sign up to set email alerts
|

Terpenes from Forests and Human Health

Abstract: Forest bathing has beneficial effects on human health via showering of forest aerosols as well as physical relaxation. Terpenes that consist of multiple isoprene units are the largest class of organic compounds produced by various plants, and one of the major components of forest aerosols. Traditionally, terpene-containing plant oil has been used to treat various diseases without knowing the exact functions or the mechanisms of action of the individual bioactive compounds. This review categorizes various terpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(103 citation statements)
references
References 107 publications
1
100
0
2
Order By: Relevance
“…The results showed that phytoncides from trees can increase NK activity, the number of NK cells, and the expression of intracellular perforin and granzyme A/B in male subjects. In addition, essential oils derived from various plants have neuroprotective effects against neurodegenerative conditions in vivo and in vitro [47]. Other studies have also shown that alcohols, acids, alkanes, phenols, and ketones are the main aromatic volatile substances in the BF environment [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that phytoncides from trees can increase NK activity, the number of NK cells, and the expression of intracellular perforin and granzyme A/B in male subjects. In addition, essential oils derived from various plants have neuroprotective effects against neurodegenerative conditions in vivo and in vitro [47]. Other studies have also shown that alcohols, acids, alkanes, phenols, and ketones are the main aromatic volatile substances in the BF environment [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the concentrations of these compounds are not affected by either the digestion process or by the oxidation reactions that took place during this process. The preservation of these compounds during digestion, and by extension, their in vitro bioaccessibility to be absorbed, is of great interest, due to the biological activities attributed to them [38]. Table 5.…”
Section: In Vitro Bioaccessibility Of Some Minor Components Of Virginmentioning
confidence: 99%
“…녹지지역은 녹지를 바탕으로 하는 지역 개념으로 (Shin, 2012), 인간의 신체건강뿐만 아니라 심리발달 및 정신건강에 도 긍정적인 영향을 주는 것으로 보고되었다 (Kim et al, 2013;Baek and Park, 2014;Cho et al, 2017). 또한 학교 주변의 자연환경은 대도시에서 살아가고 있는 초등학생에 게 긍정적인 자연과의 연계성과 자아개념에 영향을 준다 (Tak et al, 2013).…”
Section: 빈곤 녹지지역과 아동의 건강unclassified